Sustained attention and inhibitory control: age and sex related difference in children and adolescents using a CPT with distracting events - Rivella, Carlotta; Viterbori, Paola; Usai, Maria Carmen (Frontiers in Psychology, 2025)
IntroductionThe study investigates age and sex-related differences in sustained attention and inhibitory control in a sample of children and adolescents using a continuous performance test with distractor events. In addition, the impact of distractors on sustained attention and inhibitory control is explored.MethodsThe study included 479 individuals aged 6–17 years and analyzed four indices, namely omission, timing, impulsivity, and hyperactivity.ResultsResults revealed that both sustained attention and hyperactivity show age-related changes into adolescence, whereas impulsivity shows age-related changes only in the 6–12 age range, with no differences observed from 13 to 17. Sex differences emerged in inhibitory control: impulsivity remained consistently lower in females than in males across the entire 6–17 age range. In contrast, sex differences in hyperactivity were no longer evident by age 17. Overall, combined distractors have the greatest negative impact on performance, followed by visual and auditory distractors. However, in adolescents, lower distractors impact emerged, together with a positive impact of the auditory ones.DiscussionThese findings provide helpful insight on sustained attention an inhibitory control development, showing different trajectories for impulsivity and hyperactivity. In addition, insight on the role of distractors in determining the performances emerged.